Sexual harassment, the abuse of power and the crisis of leadership: "superstar" harassers and how to stop them - Beggan, James K. (New horizons in leadership studies, 2019)
Contents: 1. A socio-evolutionary approach to sexual harassment -- 2. A utility model of sexual approach -- 3. An evolutionary perspective on sexual harassment -- 4. A transactional analysis of sexual harassment -- 5. Sexual harassment as a social problem -- 6. The history of sexual harassment -- 7. Superstars, toxicity, and sexual harassment -- 8. Consensual relations and sexual harassment -- 9. Sexual harassment training through shaming -- 10. Sexual harassment and the future: Where do we go from here? -- Index.